Utility of the EULAR Sjögren syndrome disease activity index in Japanese children: a retrospective multicenter cohort study - Naomi Iwata; Minako Tomiita; Ichiro Kobayashi; Yusaburo Inoue; Yukiko Nonaka; Nami Okamoto; Hiroaki Umebayashi; Ryoki Hara; Yasuhiko Ito; Yasunori Sato; Masaaki Mori (BMC, 2020)
Abstract Background The European League Against Rheumatism (EULAR) Sjögren Syndrome Disease Activity Index (ESSDAI) has been utilized to assess Sjögren syndrome-related systemic involvement in adult patients. To date, however, the ESSDAI has not been validated in children with primary Sjögren's syndrome. This study evaluated the applicability of the ESSDAI to Japanese children with primary Sjögren's syndrome. Methods The medical records of children who had been diagnosed with Sjogren syndrome at age ≤ 16 years between June 2011 and October 2016 were collected, and their ESSDAIs at initial presentation were calculated. Clinical symptoms and treatment regimens were surveyed by questionnaire, and patients were divided into groups based on ESSDAI and glucocorticoid dosages. The associations of ESSDAI scores with treatment regimens were analyzed statistically. Results The study subjects included 31 children (3 boys, 28 girls) with primary Sjögren's syndrome. Their median age at disease onset was 10 years (interquartile range [IQR], 8-13 years), and their median initial ESSDAI was 7.0 (IQR; 5.0-15.0). ESSDAI-determined disease activity was high in nine patients (29.0%), moderate in 15 (48.4%), and low in seven (22.6%). During the first year after their initial visit, 14 patients (45.2%) were treated with prednisolone (PSL) and six (19.4%) with immunosuppressants. Dose of PSL was significantly associated with ESSDAI score. Median ESSDAI score was significantly higher in patients treated with high/medium- than with no/low-dose PSL (16.5 [IQR 10.5-18.0] vs 5.0 [IQR 3.0-8.5]). Eight (66.7%) of 12 patients administered medium/high-dose PSL and one (5.3%) of 19 administered no/low-dose PSL had high disease activity on ESSDAI. Conclusion Disease activity assessed by ESSDAI tended to be consistent with disease activity assessed by pediatric rheumatologists in determining treatment regimens. ESSDAI is useful for assessing disease activity in Japanese children with primary Sjögren's syndrome.